Parental socioeconomic position and risk of autism spectrum disorders in offspring: A cohort study of 9, 648 individuals in Denmark 1976-2013. (December 2018) - Hegelund, Emilie Rune; Flensborg-Madsen, Trine; Vassard, Ditte; Rosenblum, Leonard A.; Reinisch, June Machover; Mortensen, Erik Lykke
Highlights: Parental SEP is positively associated with ASD in offspring in crude analyses. However, an inverse association is observed after adjustment for calendar year. Parental childhood socioeconomic position modifies the investigated association. Abstract: Background: The results of studies of the association between parental socioeconomic position (SEP) and risk of autism spectrum disorder (ASD) in offspring are inconsistent, perhaps due to contextual differences in health care systems and their influence on risk of ASD diagnosis among different socioeconomic groups. The present study investigated the association between parental SEP in adulthood and risk of ASD diagnosis in offspring in a Nordic welfare state and whether this association was modified by parental childhood SEP. Method: The study population comprised 9648 live-born singletons who were followed in the Psychiatric Central Register from birth in 1976–1996 until 2013. Cox regression was used to estimate hazard ratios for ASD diagnosis according to parental SEP in adulthood. Results: The crude results showed a tendency towards higher parental SEP in adulthood being associated with higher risk of ASD diagnosis in offspring. However, the association was reversed after adjustment for possible confounders. The reversion of the direction of the association was entirely attributable to the strong confounding effect of calendar year. Further, the results showed that parental childhood SEP modified the association between parental SEP in adulthood and risk of ASD diagnosis in offspring. Conclusions: Both methodological and contextual issues may be of great importance for the observed association between parental SEP and risk of ASD diagnosis in offspring. Particularly, the secular trends in ASD diagnoses seem to be of great importance suggesting that changes in diagnostic patterns may influence the association between parental SEP and risk of being diagnosed with ASD.